A universal and passive power management circuit with high efficiency for pulsed triboelectric nanogenerator. (February 2020) - Qin, Huaifang; Gu, Guangqin; Shang, Wanyu; Luo, Hongchun; Zhang, Wenhe; Cui, Peng; Zhang, Bao; Guo, Junmeng; Cheng, Gang; Du, Zuliang
Abstract: The power management circuit greatly improves the energy storage efficiency of triboelectric nanogenerator (TENG), but the presence of active electronic components in the circuit increases the energy consumption and improves the complexity of the circuit. Here, a passive power management circuit without any active components is designed based on Pulsed-TENG. Theoretical calculation results show that the equivalent impedance of the Pulsed-TENG is zero. The simulations show that the output voltage and energy of the Pulsed-TENG can still reach the maximum values, as the load resistance is as low as 0.001 Ω. These means that the challenging problem of impedance mismatching between TENG and power management circuit is well solved. In simulation and actual test, the energy storage efficiency of the passive power management circuit for Pulsed-TENG can reach 83.6% and 57.8%, respectively. The working principle and affecting factors of the circuit have been discussed, and it is also demonstrated to drive calculator and temperature hygrometer. The passive power management circuit reported here with simple structure, low cost, and high efficiency is a universal design for general Pulsed-TENGs with AC signals, which has promising applications in the self-powered electronic devices and the Internet of Things. Graphical abstract: This paper developed a universal and passive power management circuit with high efficiency for pulsed triboelectric nanogenerator (Pulsed-TENG) . All the electronic components in the circuit are passive and simple. Simulation results show that the energy storage efficiency of the passive power management circuit can reach 83.6%. In the actual charging test, the energy storage efficiency is 57.8%. Image 1 Highlights: A universal passive power management circuit is designed without any active components based on Pulsed-TENG. Theoretical calculation results show that the equivalent impedance of the Pulsed-TENG is zero. The key problem of impedance mismatching between TENG and power management circuit was well solved. The energy storage efficiency and speed were greatly improved and the size of each component in the circuit is reduced.